Enterprise networking multilayer switching and applications - Theoharakis, Vasilis, 1967-; Serpanos, Dimitrios Nikolaou; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2002)
Primarily targeted toward the network or MIS manager who wants to stay abreast of the latest networking technology, this title offers up to date information relevant for the design of modern corporate networks and for the evaluation of new networking equipment. The book describes the architectures and standards of switching across the various protocol layers and will also address issues such as multicast quality of service, high-availability and network policies that are requirements of modern switched networks.
1. The OSI model and switching / Vasilios A. Siris -- 2. Network service availability and performance / Mike Fisk -- 3. Management and control of intelligent optical networks / Dimitrios Pendarakis and Subir Biswas -- 4. Virtual local area networks / Cam Cullen -- 5. IP switching and MPLS / S. Manikantan -- 6. Web switching / Vishal Sharma, Rakhi Sharma -- 7. Multilayered quality of service / Luiz A. DaSilva -- 8. Voice over IP : protocols and technical hurdles / Mahbub Hassan and Sanjay Jha -- 9. Voice over Internet protocol (VoIP) : evaluation of technologies for deployment / Bhumip Khasnabish -- 10. Interactive video on enterprise networks / Christine Perey -- 11. Emerging enterprise storage systems : storage or system area networks (SANs) / Bhumip Khasnabish -- 12. Managing security in modern enterprise networks / S. Raj Rajagopalan -- 13. Web caching : a survey / Antonis Danalis and Evangelos Markatos -- 14. Linux systems as network infrastructure components / Tony Mancill.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web.
Title from PDF t.p. (viewed on May 25, 2010).
Keywords: Business enterprises -- Computer networks; Local area networks (Computer networks); Wide area networks (Computer networks); Electronic books